Characterization of Seashell Waste through Calcination Process - Sarah Dampang; Endah Purwanti (CHEMICA: Jurnal Teknik Kimia, 2020)
Seashell waste found in Tanjung Baru Beach, Karawang, which has not fully utilized. This waste can be widely used as an environmentally friendly material in various fields. Seashell waste is the source of CaCO3, and throughout the calcination process at the correct temperature, it can be converted to CaO. The purpose of the calcination process is to obtain a solid CaO by releasing CO2 gas. The calcination process can carry out at temperatures of 800 ℃, 900 ℃, and 1000 ℃ with a calcination time of 2 hours, 3 hours, and 4 hours. The seashell waste is characterized and analyzed using the Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy, and Energy Dispersive X-Ray (SEM-EDX). Before and after the calcination process, the FTIR spectrum of seashells is around 710 cm-1- 1476 cm-1, a characteristic peak of the C-O group from CaCO3.  The spectrum of 3429 cm-1- 3468 cm-1 is a characteristic peak of the O-H group from Ca(OH)2. The spectrum 2513.25 cm-1 is a characteristic peak of the C-H group containing CaO appearing after calcination. The seashell powder is analyzed by using SEM-EDX with the result where the most dominant elements are C (18.43%), O (52.07%), and Ca (27.86%) from the calcined shells. The elements C, Na, Al, Si, Fe, and Cu, are zero due to the heating process (calcination). The calcined seashell has also shown a rough surface and irregularly shaped particles.